PENGARUH SENAM DIABETES TERHADAP PENURUNAN KADAR GULA DARAH PADA KLIEN DIABETES MELITUS TIPE 2 YANG MENGGUNAKAN OBAT HYPOGLIKEMIK ORAL - Suarti, Ni Made (Jurnal Kesehatan Holistic, 2017)
Diabetes mellitus (DM) is a chronic multisystem disease associted with normal insulin production, insulin impaired, or both. This disease need sustainable care that requires self management and client support to prevent long-term complications, one of this care is foot excercise. This study uses a quasi-experimental design with post test only non equivalent control group. The research sample is 38 participants to review each of the control group and intervention group, taken by purposive sampling. The result of this study showed significant differences decrease in blood sugar levels between intervention group and control group 3 weeks after study (p value 0,000 <0,05 and into week 6 research (p value 0,000 <0.5) compared with initial blood sugar levels. Gymnastics diabetes regularly is important to control blood sugar levels in addition to keep taking oral medication and meal hypoglikemik accordance with the previously programmed.